2019
DOI: 10.1111/jfpp.14362
|View full text |Cite
|
Sign up to set email alerts
|

Impact of critical high‐intensity pulsed electric field processing parameters on oxidative enzymes and color of broccoli juice

Abstract: This research evaluated the influence of high‐intensity pulsed electric field (HIPEF) processing parameters, electric field strength, treatment time, and polarity on color difference (∆E*), polyphenol oxidase (PPO), and lipoxygenase (LOX) activities in broccoli juice. An optimization of HIPEF processing was accomplished and compared with thermal treatment (90°C/60 s). The lowest RALOX (68.71%) and RAPPO (36.11%) were reached at the strongest HIPEF conditions (35 kV/cm for 2,000 µs in bipolar mode). Bipolar mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49]. Another study of enzyme activity in strawberry puree reported only 3% residual PPO activity after high-intensity PEF at 35 kV/cm, a frequency of 229 Hz, a pulse width of 3.2 and 4.2 µs, treatment time of 1500 µs and bipolar pulses [50], while the minimal residual activity in broccoli juice reached 36% after highintensity PEF (35 kV/cm, 986 kJ/m³, treatment time 2000 µs, bipolar pulse), while lower Compared to other studies, a decrease in the POD and PPO activity to 70% and 55% of the initial activity, respectively, was observed in kale puree after thermal treatment at 70 • C for 2 min [44], while a thermal treatment at 72 • C for 15 s of apple juice, 90 • C for 15 min of strawberry puree and 90 • C for 60 s of broccoli juice resulted in (almost) complete inactivation of POD and PPO [13,47,48]. A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49].…”
Section: Residual Enzyme Activity Of Peroxidase (Pod) and Polyphenolocontrasting
confidence: 64%
See 2 more Smart Citations
“…A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49]. Another study of enzyme activity in strawberry puree reported only 3% residual PPO activity after high-intensity PEF at 35 kV/cm, a frequency of 229 Hz, a pulse width of 3.2 and 4.2 µs, treatment time of 1500 µs and bipolar pulses [50], while the minimal residual activity in broccoli juice reached 36% after highintensity PEF (35 kV/cm, 986 kJ/m³, treatment time 2000 µs, bipolar pulse), while lower Compared to other studies, a decrease in the POD and PPO activity to 70% and 55% of the initial activity, respectively, was observed in kale puree after thermal treatment at 70 • C for 2 min [44], while a thermal treatment at 72 • C for 15 s of apple juice, 90 • C for 15 min of strawberry puree and 90 • C for 60 s of broccoli juice resulted in (almost) complete inactivation of POD and PPO [13,47,48]. A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [47,49].…”
Section: Residual Enzyme Activity Of Peroxidase (Pod) and Polyphenolocontrasting
confidence: 64%
“…Compared to other studies, a decrease in the POD and PPO activity to 70% and 55% of the initial activity, respectively, was observed in kale puree after thermal treatment at 70 °C for 2 min [ 44 ], while a thermal treatment at 72 °C for 15 s of apple juice, 90 °C for 15 min of strawberry puree and 90 °C for 60 s of broccoli juice resulted in (almost) complete inactivation of POD and PPO [ 13 , 47 , 48 ]. A study further compared low and high-intensity PEF treatments (12 kV/cm, 80 and 130 kJ/kg) of apple juice, leading to the partial inactivation of POD and PPO for the low PEF treatment (comparable to the observations in our results) and a higher inactivation for the high-intensity PEF treatment, suggested to be related to the thermal impact occurring due to dissipating energy as a result of Joule heating during the PEF treatment [ 47 , 49 ].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Coatings can provide moisture and gas permeability barriers and thus help with microbial growth control and protection of color and texture (Bourtoom, 2008; Hosseini et al., 2017; Mousavian et al., 2021). One example of a novel edible coating for storehouse fruit is aloe vera (AV; Sánchez‐Vega et al., 2020; Serrano et al., 2006). AV possesses antifungal protection against numerous pathogenic fungi such as Botrytis cinerea (De Rodrıguez et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was speculatively attributed to the increased SFN content in the extract, but this was not confirmed experimentally. Other studies report about the effect of high intensity pulsed electric fields (HIPEF), using voltage of 15 kV/cm or higher, on broccoli juice (Sánchez‐Vega, Elez‐Martínez, & Martín‐Belloso, 2015; Sánchez‐Vega, Garde‐Cerdan, Rodriguez‐Roque, Elez‐Martinez, & Martin‐Belloso, 2020; Sánchez‐Vega, Rodríguez‐Roque, Elez‐Martínez, & Martín‐Belloso, 2020). The authors used the technology for broccoli juice preservation aiming at minimizing the loss of bioactive compounds other than SFN.…”
Section: Introductionmentioning
confidence: 99%